Coordinated active and reactive power control for distribution networks with high penetrations of photovoltaic systems. (1st January 2022) - Hu, Ruonan; Wang, Wei; Wu, Xuezhi; Chen, Zhe; Jing, Long; Ma, Wei; Zeng, Guohong
Highlights: A novel coordinated active and reactive power optimization method is developed. Distribution network voltage variations caused by PV power fluctuations are solved. Distribution network has high penetrations of PV power generation systems. Abstract: A primary concern of the large-scale application of photovoltaic (PV) power systems in distribution networks is nodal voltage fluctuations caused by active power fluctuations of PV. Therefore, this paper proposes a novel coordinated active and reactive power optimization method for distribution networks with high penetrations of PV systems, which can reduce bus voltage fluctuations, active power curtailments of PV, operating losses of distribution networks, and adjustments of conventional voltage regulation devices such as on-load tap changers (OLTCs) and capacitor banks (CBs). The proposed method coordinates the OLTC, CBs, and PV and BESS plants in two levels. The upper level establishes a mixed integer nonlinear programming (MINP) model based on the model predictive control (MPC), which can properly plan the operation of the OLTC, CBs, and PV, and a modified NSGA-II algorithm is developed to find the best solution of the MINP model. The lower level employs the leader–follower consensus algorithm (LFCA) to coordinate the charging power and reactive power of distributed battery energy storage systems (BESSs) to control real-time bus voltage fluctuations. The LFCA based control method can make BESSs fairly participate in the real-time voltage regulation of each feeder. Case studies are conducted on a modified IEEE 33-bus distribution network system, utilizing the actual active power data of a PV plant. Simulation results indicate that the proposed method can effectively control bus voltage variations of all feeders within the pre-defined range, and the distribution network can operate with higher penetrations of PV power systems, lower losses, and better economy.